2020
DOI: 10.1088/1757-899x/788/1/012091
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative investigations on the stability of Al2O3-SiO2 hybrid water-based nanofluids

Abstract: Qualitative experiments were carried out to investigate the stability of Al2O3-SiO2 hybrid water-based nanofluids. The main nanoparticles used in this work were Al2O3 and SiO2 since these types of nanoparticles has been widely used and proposed in many applications and information on their hybrid dispersion stability characteristic are still elusive. The present work demonstrated the stability of Al2O3-SiO2 hybrid nanofluids using various preparation techniques and successively elucidating the optimum preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The measured weight was then converted into the volume of the nanoparticles and then successively suspended in the designated volume of the base fluid to achieve a concentration of C= 0.001 vol%. Prior to the final dilution process, the suspension was then stirred for 15 minutes using a magnetic stirrer to achieve homogeneity and was then sonicated in an ultrasonic bath (Bransonic® CPXH Ultrasonic Bath) for 1 hour just before the experiments were conducted, based on our previous work [26]. During the preparation process, no dispersant or surfactant was added to avoid altering the fluid's chemical and thermo-physical properties.…”
Section: Methods and Materials Nanofluid Preparationmentioning
confidence: 99%
“…The measured weight was then converted into the volume of the nanoparticles and then successively suspended in the designated volume of the base fluid to achieve a concentration of C= 0.001 vol%. Prior to the final dilution process, the suspension was then stirred for 15 minutes using a magnetic stirrer to achieve homogeneity and was then sonicated in an ultrasonic bath (Bransonic® CPXH Ultrasonic Bath) for 1 hour just before the experiments were conducted, based on our previous work [26]. During the preparation process, no dispersant or surfactant was added to avoid altering the fluid's chemical and thermo-physical properties.…”
Section: Methods and Materials Nanofluid Preparationmentioning
confidence: 99%
“…Their measurements revealed that the values of zeta potential for all ratios were in the range of ±27 ~ +39.54 mV, which indicates a moderate upward stability. Also, Ismail et al [13] applied a variety of ultrasonic and stirrer times for dispersing Al2O3-SiO2 hybrid nanofluid. Then, for two weeks, they measured the stability of the Al2O3-SiO2 hybrid nanofluid using an observation method.…”
Section: Introductionmentioning
confidence: 99%
“…From his studies it is concluded that tri-hybrid nanoparticles effectively prepared and attained stability. The qualitative studies on the stability of Al2O3-SiO2 based water hybrid nanofluid was carried out by H. Ismail [23]. The enhanced stability, optical properties and high solar heat transformation competency of SiC-MWCNTs hybrid nanofluids for DASC applications was studied by Xiaoke Li [24].…”
Section: Introductionmentioning
confidence: 99%